Hubungan Self Efficacy dan Minat Belajar dengan Hasil Belajar Siswa pada Mata Pelajaran Agama Islam Bagi Siswa di SMP Negeri 3 Palembang - Muthmainnah Muthmainnah; Nyayu Khodijah; Ermis Suryana (Bahasa Indonesia, Bahasa English, 2020)
The main problem in this study is whether there is a significant relationship between self efficacyand student learning outcomes of PAI subjects in SMP Negeri 3 Palembang, whether there is a significant relationship between learning interest and student learning outcomes in Islamic Religious Education subjects at SMP Negeri 3 Palembang, and whether there is a significant relationship between self efficacyand interest in learning together with student learning outcomes in Islamic Religious Education subjects at SMP Negeri 3 Palembang. The purpose of the study was to analyze the significant relationship between self efficacyand student learning outcomes in Islamic Religious Education subjects at SMP Negeri 3 Palembang, to analyze the significant relationship between learning interest and student learning outcomes in Islamic Religious Education subjects at SMP Negeri 3 Palembang, and to analyze significantly between self efficacyand interest in learning together with student learning outcomes of Islamic Religious Education subjects at SMP Negeri 3 Palembang. The type of this research is the type of correlation research. In this study, the research sample was 60 students. Data collection techniques are observation, documentation and questionnaire. The data analysis technique is through quantitative descriptive analysis.First research results, based on the results of the hypothesis test showed that there was a positive relationship between self-efficacy and learning outcomes of Islamic Religious Education subjects in SMP Negeri 3 Palembang, r count of 0.546 with a significant level of 5%. Secondly, based on the results of the hypothesis test, there is a positive relationship between learning interest and the learning outcomes of Islamic Religious Education subjects in SMP Negeri 3 Palembang, r count of 0.773 with a significant level of 5%. Third, based on theresults of hypothesis testing, there is a positive relationship between self efficacyand interest in learning together with the learning outcomes of Islamic Religious Education subjects in SMP Negeri 3 Palembang with a multiple regression value of 0.773 with a significant level of 5%.